Online learning in Indonesian higher education: New indicators during the COVID-19 pandemic - Fairusy Fitria Haryani; Sarwanto Sarwanto; Dwi Maryono (International Journal of Evaluation and Research in Education (IJERE), 2023)
The COVID-19 pandemic has increasingly demanded the implementation of online learning in Indonesia. This study aimed to determine the indicators influencing the effectiveness of online learning in Indonesian higher education during the COVID-19 pandemic. The study employed a mixed-methods approach. We conducted an online survey of 201 lecturers teaching courses during the even semester of 2019/2020 and 1,983 students in 18 higher educations then followed up with an online interview with the lecturers, the head of the study program, and the institute of quality assurance of four chosen institutions. The results showed that besides the lecturer’s information technology capabilities, the new indicators of online learning effectiveness in higher education during the COVID-19 pandemic were the availability of assessment guidelines, semester learning plan guidelines, academic position, type of lecturer publication, lecturer certification, and workload.